2018
DOI: 10.1007/s10535-018-0799-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptation and gene expression analysis of Casuarina equisetifolia under salt stress

Abstract: Casuarina equisetifolia is widely planted in coastal areas of tropical and subtropical regions as windbreaks or to stabilize dunes against wind erosion due to its high salt tolerance and nitrogen-fixing ability. To investigate the mechanisms responsible for its salt tolerance, we examined growth, mineral composition, expression of genes for sodium (Na +) and potassium (K +) transport proteins, and antioxidant responses under NaCl treatments. Increasing NaCl concentrations inhibited lateral root elongation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Their roots were washed and the plants were transferred to containers filled with clean water and allowed to grow for 2 weeks until new roots appeared. Plants were then transferred to Hoagland solution containing 200 mM NaCl based on a previous study ( Fan et al, 2018 ) and allowed to grow for varying durations. The solution was replaced with fresh solution every day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their roots were washed and the plants were transferred to containers filled with clean water and allowed to grow for 2 weeks until new roots appeared. Plants were then transferred to Hoagland solution containing 200 mM NaCl based on a previous study ( Fan et al, 2018 ) and allowed to grow for varying durations. The solution was replaced with fresh solution every day.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, C. glauca tolerates high levels of salinity by changing the levels of some neutral sugars, proline, and ornithine ( Jorge et al, 2017 ). In addition, greater amounts of Na + are adsorbed over the roots under salt stress, and expression of NHX and SOS genes in roots helps to maintain K + balance, an essential part of the response to excess salt in C. equisetifolia ( Fan et al, 2018 ). However, the unique strategies adopted by these plants for dealing with salinity and the salt-tolerance mechanisms of these species remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in C. obesa, the tolerance to high salinity levels was related to the exclusion of ions (Carter et al 2006a;Isla et al 2014), osmotic adjustments, accumulation of compatible organic solutes, and photoprotective mechanisms (Carter et al 2006a,b). Accordingly, ion extrusion (Fan et al 2018;Gupta et al 2018) and osmolyte accumulation (Tani and Sasakawa 2006) were also implicated as important salt tolerance mechanisms in C. equisetifolia. In this species, ion translocation to shoots and retention in roots were observed, suggesting the existence of alternative mechanisms to protect cells from Na + (Selvakesavan et al 2016).…”
Section: Mechanisms Underlying Salt-tolerancementioning
confidence: 99%
“…Hence, it helps to improve the ecological environment by providing materials (Djighaly et al 2018;Ye et al 2019). As a coastal shelterbelt species, C. glauca is mainly exposed to Na + and Cl − toxicity (Fan et al 2018;Vikashini et al 2018). Djighaly et al (2018) found that C. glauca was more tolerant to NaCl stress than C. equisetifolia, and inoculation with AMF could improve the uptake of nutrients (such as N and P) and water of C. glauca under NaCl stress.…”
Section: Introductionmentioning
confidence: 99%